The modernization of the market places in the district of Bogotá (2014)
This essay aims to raise awareness of the actors and processes that allow carrying out the modernization of a market place in the district, and the difficulties that have arisen along administrations in the Bogotá City Hall to take out the execution of such projects. The implementation of land use plans can better plan and govern a city within planning instruments regularization schemes and management tool that is oriented setting are necessary conditions for optimal functioning of communal uses of floor and do not have a building permit, in this way is achieved mitigate the negative impact of the environment and improvement of the physical structure of these facilities.